Anticancer and antimicrobial properties of novel η6-p-cymene ruthenium(ii) complexes containing a N, S-type ligand, their structural and theoretical characterization. Issue 66 (27th November 2019) - Namiecińska, Ewelina; Sadowska, Beata; Więckowska-Szakiel, Marzena; Dołęga, Anna; Pasternak, Beata; Grazul, Magdalena; Budzisz, Elzbieta
Abstract : New arene–ruthenium(ii ) complexes with pyrazole derivatives as ligands were synthesized and characterized. This compounds exhibited good cytotoxic effects, and strong biostatic and biocidal activity. Abstract : Ruthenium(ii ) complexes are lately of great scientific interest due to their chemotherapeutic potential as anticancer and antimicrobial agents. Here we present the synthesis of new pyrazole carbothioamide derivatives and their four arene–ruthenium complexes. The title compounds were characterized with the application of IR, NMR, mass spectrometry, elemental analysis and X-ray diffraction. Additionally, for new complexes DFT calculations were done. Their antimicrobial activity (MIC, MBC/MFC) was examined in vitro against Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecalis, Pseudomonas aeruginosa, Proteus vulgaris and Candida albicans . Their cytotoxic effects, using the MTT assay, against three cancer cell lines: HL-60, NALM-6, WM-115 and normal human foreskin fibroblasts (HFF-1) were also investigated. The influence of the new arene–ruthenium(ii ) complexes on the DNA structure was also tested. From our results, compound 2d showed higher cytotoxicity against melanoma cell line WM-115 than cisplatin. Strong biostatic and biocidal activity of the tested complexes against Gram-positive bacteria, including S. aureus, S. epidermidis and E. faecalis was demonstrated. The new arene–ruthenium(ii ) compounds could not only inhibit proliferation of cancer cells, but also protect patients against malignant wound infections.